The Impact Covid-19 Outbreak, Green Finance, Creativity and Sustainable Economic Development on the Economic Recovery in G20 Countries - Miar, Miar; Neneng, Sunaryo; Sui, Jeky Melkianus (International Journal of Energy Economics and Policy, 2022)
Economic growth has become a global issue, especially after Covid-19, and attain the focus of recent studies and policymakers. A question that repeatedly arises when compulsion of sustainability is sought in a system and economies are obligated to strive for creative outcomes in order to increase economic efficiency. Meanwhile, green financing and sustainable economic development are also expected to be a part of the requirement as they are directly or indirectly indicators of economic growth. Thus, the current research examines the role of the Covid-19 outbreak along with green finance, sustainable economic development and creativity on the economic recovery in the context of G20 economies. This study has used the World Development Indicators (WDI) to extract the data of the selected countries from 2016 to 2020. The present study has also executed the robust standard error along with the fixed-effect model (FEM) to examine the nexus among the variables. The results revealed that green finance (green credit and renewable energy production), sustainable economic development environmental dimension (GHG emissions) and creativity have a positive association with economic growth in G20 countries. These outcomes are suitable for the new researchers while studying this area in the future and helpful for the regulators while developing the regulation related to the economic recovery.